Redox stability and electrical conductivity of Fe2.3Mg0.7O4 +/-delta spinel prepared by mechanochemical activation - Domingues, E. M.
This paper addresses the potential of mechanochemical activation of MgO and alpha-Fe2O3 precursor powders to obtain Fe2.3Mg0.7O4 ceramics with enhanced redox stability and electrical conductivity. X-ray diffraction (XRD) and Mossbauer spectroscopy suggest the initial formation of the spinel phase after 5 h of high-energy milling in inert gas, but after 10 h of mechanoactivation, the precursor still comprised hematite as a major phase with minor amounts of magnesiowustite as by-product. The activated mixtures can be nearly completely converted to spinel solid solution by heating to 1173 K, whereas single-phase, dense spinel ceramics can be prepared by sintering at 1773 K in inert atmosphere. These ceramics demonstrated redox stability under mildly reducing conditions (p(O-2) similar to 10 Pa), as confirmed by XRD, thermogravimetry and electrical measurements. The electrical conductivity of Fe2.3Mg0.7O4 at this oxygen partial pressure is lower compared to magnetite, but it is still as high as 60 S/cm at 1073 K and 15 S/cm at room temperature. Cooling below 1473 K in air results in a drop of conductivity due to segregation of hematite phase at the grain boundaries. However, the phase separation is kinetically stagnated at 1073 K, and, after slight initial degradation, the retained electrical conductivity is more than 3 orders of magnitude higher compared to hematite and MgFe2O4 spinel. (C) 2013 Elsevier Ltd. All rights reserved.